The Influence of Tutorial-Based Learning Model on Information and Communication Technology (ICT) Subjects at Junior High School Painan - Helmiza; Ganefri; Ambiyar; Irfan, Dedy (The Indonesian Journal of Computer Science, 2023)
This study aims to determine the effect of learning outcomes using a tutorial-based learning model in Information and Communication Technology (ICT) subjects at Junior High School 02 Painan. This study uses a quasi-experimental research method. The population in this study were students of class VIII Junior High School 02 Painan. The sample in this study used a random sampling technique with students in class VIII A as the experimental class and VIII B as the control class with 30 students in class A and 25 students in class B. The research instrument used was objective questions which were tested for validity, reliability, discriminatory power, and level of difficulty. Data were analyzed with parametric statistics including normality test, homogeneity test and hypothesis testing. As well as to test the activity and response of the research instrument used was a questionnaire which was validated by three lecturers who are experts in learning evaluation and the results of effectiveness were analyzed based on classical completeness and based on the Gain Score. The results of this study revealed that student learning outcomes using the tutorial-based learning model with an average score of the experimental class was 78.933 better than ordinary learning with an average score of the control class was 69.76 in the final test analysis where the tcount was 9.484 and ttable is 1.68 with a significance level of 95% so that tcount > ttable and the research hypothesis is accepted. As well as seen from the activeness and response of students, the average result of activity is 80.9% with a very good classification and for the average student response result is 87.4% with a very good classification result. The effectiveness of learning using a tutorial-based learning model in the effectiveness trial, obtained 87% of students scored ≥ 70 which stated classically effectiveness and for the control class obtained 43.33% of students scored < 70 which stated that it was not classically effective. And in terms of Gain Score gets a value of 37.31% (medium). Thus it can be concluded that there is an influence of the tutorial-based learning model on Information and Communication Technology (ICT) learning on student learning outcomes.